KARNESIA Flashcard Assisted by QR Code in Elementary School - Rahmadhanti, Naflah Dikta; Cholifah, Puri Selvi; Khotimah, Khusnul (Faculty of Education Universitas Negeri Malang, 2023)
The KARNESIA flashcard assisted by QR Code is a research development product in the form of a learning media in the form of a flashcard assisted by a QR Code with the product name KARNESIA. Based on the results of field trials, this product obtained validation results according to two media experts with an average of 96.4%. The validation of two material experts obtained an average score of 88.75%. The practicality and attractiveness of the product scored 94% and 98.8%, respectively. KARNESIA includes very valid, practical, and interesting criteria to be used in learning for fourth-grade elementary school.